Successful term pregnancy following cervical cerclage for uterine atrophy secondary to childhood radiotherapy. Issue 8 (1st August 2022) - Martin, Anastasia; Suff, Natalie; Shennan, Andrew
Abstract : Pelvic radiotherapy can lead to scarring and atrophy of reproductive organs including the uterus. This may lead to complications, such as preterm birth, during pregnancy. The mechanism by which preterm birth is associated with pelvic radiation is believed to be due to inefficient uterine stretch or a deficient cervix. We report a case of cervical shortening during the second trimester in a pregnant woman with a history of pelvic radiotherapy in childhood. Ultrasound surveillance and cervical cerclage inserted in the shortening cervix successfully prevented preterm labour in this case. Cerclage insertion led to a longer cervix and lower fibronectin. Although cervical cerclage does not influence uterine stretch, it may be able to prevent cervical dilatation and therefore prevent ascending infections and subsequent inflammatory sequelae which results in preterm labour. We recommend cervical surveillance and targeted cerclage interventions to prevent preterm labour in women with prior childhood pelvic radiotherapy.